2021
DOI: 10.1186/s12871-021-01518-z
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on fluid therapy management in surgical adult patients

Abstract: Background Perioperative fluid therapy management is changing due to the incorporation of different fluids, surgical techniques, and minimally invasive monitoring systems. The objective of this study was to explore fluid therapy management during the perioperative period in our country. Methods We designed the Fluid Day study as a cross-sectional, multicentre, observational study. The study was performed in 131 Spanish hospitals in February 2019. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Nevertheless, most of the available literature continues to focus on resuscitation fluids. Studies now confirm the benefits of avoiding excessive 0.9% NaCl administration, including reduced risk of mortality or major complications such as myocardial infarction, in favor of balanced crystalloids, with a consensus that this is especially true in patients with sepsis, burns and diabetic keto-acidosis, but not for those with traumatic brain injury where saline should still be preferred [ 38 ]. Although the magnitude of benefit may be small in controlled studies, in the ‘real world’ volumes of fluid are not precisely controlled and many excess liters of fluid may be given.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most of the available literature continues to focus on resuscitation fluids. Studies now confirm the benefits of avoiding excessive 0.9% NaCl administration, including reduced risk of mortality or major complications such as myocardial infarction, in favor of balanced crystalloids, with a consensus that this is especially true in patients with sepsis, burns and diabetic keto-acidosis, but not for those with traumatic brain injury where saline should still be preferred [ 38 ]. Although the magnitude of benefit may be small in controlled studies, in the ‘real world’ volumes of fluid are not precisely controlled and many excess liters of fluid may be given.…”
Section: Resultsmentioning
confidence: 99%
“…One cross-sectional, multicenter, observational study of fluid management in more than 7000 patients reported a high degree of variability in perioperative volume delivered. Moreover, advanced fluids monitoring strategies were only used in 5% and 10% of patients in the intraoperative and postoperative periods, respectively [ 38 ]. Improving basic fluid administration on medical and surgical wards is achievable with better education and standardization of use.…”
Section: Resultsmentioning
confidence: 99%
“…A larger sample size may have yielded more conclusive clinical results. Second, our study focused only on the management of realistic conditions, and did not consider other factors that can contribute to PPCs, such as opioid dosage and fluid therapy [ 22 ]. Therefore, further well-designed, large-scale prospective studies are needed to gain a comprehensive understanding of PPCs following procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results were based on clinical management under real-life conditions. We have not analyzed other factors, such as mechanical ventilation parameters, recruitment maneuvers, opioid doses, fluid therapy, and others that are known to increase these complications and probably need to be assessed in subsequent studies 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%